Microscopic evaluation of cadmium-induced nephrotoxicity and the protective role of date palm fruit extract - Badawy, Sara; Abd-Elraouf , Muhamad; Gab-Allah, Mahmoud S.A.; El-Mashad, Abdel-Baset I.; Tantawy, Ahmed A.; Amin, Aziza A. (Journal of Advanced Veterinary Research, 2024)
Chronic cadmium exposure is known to be a major health concern due to its nephrotoxic effects. Consequently, this study aimed to assess the potential protective effects of date palm fruit extract (DPFE) against cadmium-induced renal toxicity in male albino rats. A total of 48 rats were divided equally into four groups and subjected to specific treatments. Group I (control given 1 ml distal water orally daily), group II (200 mg DPFE /kg b.wt. orally daily), Group III (5 mg CdCl2/kg b.wt. orally, twice a week), and VI (DPFE and CdCl2). Serum samples were collected after 4 and 8 weeks for biochemical analysis, and kidney tissue specimens were obtained for histopathological examination. The administration of cadmium chloride for 4 and 8 weeks resulted in a significant (p<0.05) increase in the serum creatinine, urea, and uric acid levels, indicating kidney dysfunction. Histopathological changes, including vascular lesions, hemorrhage, edema, periglomerular, perivascular and interstitial fibrosis, mononuclear leucocytic cellular infiltration and excessive glomerular and tubular degeneration and necrosis which further confirmed the nephrotoxic effects of cadmium. However, pre-treatment with DPFE exhibited a substantial ameliorative effect against cadmium-induced nephrotoxicity. DPFE supplementation led to a significant reduction in kidney biochemical parameters toward normal levels and improved renal tissue architecture. Our findings indicate that date palm fruit extract has a time-dependant protective effect on kidney function indices and histopathological alterations induced by cadmium, highlighting its potential as a natural medication to mitigate renal damage caused by chronic cadmium exposure.